Microplastic ingestion ubiquitous in marine turtles. (4th December 2018) - Duncan, Emily M.; Broderick, Annette C.; Fuller, Wayne J.; Galloway, Tamara S.; Godfrey, Matthew H.; Hamann, Mark; Limpus, Colin J.; Lindeque, Penelope K.; Mayes, Andrew G.; Omeyer, Lucy C. M.; Santillo, David; Snape, Robin T. E.; et al.
Abstract: Despite concerns regarding the environmental impacts of microplastics, knowledge of the incidence and levels of synthetic particles in large marine vertebrates is lacking. Here, we utilize an optimized enzymatic digestion methodology, previously developed for zooplankton, to explore whether synthetic particles could be isolated from marine turtle ingesta. We report the presence of synthetic particles in every turtle subjected to investigation ( n  = 102) which included individuals from all seven species of marine turtle, sampled from three ocean basins (Atlantic [ATL]: n  = 30, four species; Mediterranean (MED): n  = 56, two species; Pacific (PAC): n  = 16, five species). Most particles ( n  = 811) were fibres (ATL: 77.1% MED: 85.3% PAC: 64.8%) with blue and black being the dominant colours. In lesser quantities were fragments (ATL: 22.9%: MED: 14.7% PAC: 20.2%) and microbeads (4.8%; PAC only; to our knowledge the first isolation of microbeads from marine megavertebrates). Fourier transform infrared spectroscopy (FT‐IR) of a subsample of particles ( n  = 169) showed a range of synthetic materials such as elastomers (MED: 61.2%; PAC: 3.4%), thermoplastics (ATL: 36.8%: MED: 20.7% PAC: 27.7%) and synthetic regenerated cellulosic fibres (SRCF; ATL: 63.2%: MED: 5.8% PAC: 68.9%). Synthetic particles being isolated from species occupying different trophic levels suggest the possibility of multiple ingestion pathways. These include exposure from polluted seawater and sediments and/or additional trophic transfer from contaminated prey/forage items. We assess the likelihood that microplastic ingestion presents a significant conservation problem at current levels compared to other anthropogenic threats. Abstract : Knowledge of the incidence and levels of synthetic particles in large marine vertebrates is lacking. Here, we explore whether synthetic particles could be isolated from marine turtle ingesta and report the presence in every turtle subjected to investigation including individuals from all the seven species of marine turtle, sampled from three ocean basins. Most particles were fibres in lesser quantities were fragments/microbeads and were a range of synthetic materials. Synthetic particles isolated from species occupying different trophic levels suggest the possibility of multiple ingestion pathways. We assess the likelihood this presents a significant conservation problem at current levels.